1998
DOI: 10.1021/js970218s
|View full text |Cite
|
Sign up to set email alerts
|

Membrane Transport of Drugs in Different Regions of the Intestinal Tract of the Rat

Abstract: Regional permeability coefficients of 19 drugs with different physicochemical properties were determined using excised segments from three regions of rat intestine: jejunum, ileum, and colon. The results are discussed in relation to the characteristics of the drug, i.e., MW (range 113-1071 Da), pKa, log D (octanol/water at pH 7.4) (range -3.1 to +2.4), and the regional change in the properties of the epithelial membrane. There was a significant decrease in permeability to hydrophilic drugs and a significant in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

15
153
0
3

Year Published

2000
2000
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 240 publications
(171 citation statements)
references
References 47 publications
15
153
0
3
Order By: Relevance
“…The values obtained for propranolol and mannitol permeability in unstripped mouse ileum are very similar to those reported for stripped rat intestine (Ungell et al, 1998) suggesting that the presence of an intact muscle layer in mouse ileum has no signi®cant e ect on passive permeability.…”
Section: Resultssupporting
confidence: 80%
See 1 more Smart Citation
“…The values obtained for propranolol and mannitol permeability in unstripped mouse ileum are very similar to those reported for stripped rat intestine (Ungell et al, 1998) suggesting that the presence of an intact muscle layer in mouse ileum has no signi®cant e ect on passive permeability.…”
Section: Resultssupporting
confidence: 80%
“…Propranolol, which has been shown to be highly permeable across intestine (Ungell et al, 1998) was used to assess the inherent passive transcellular permeability of mouse tissues. Propranolol was added to the donor chamber at a concentration of 100 mM with 0.2 mCi.ml 71 [ 3 H]-propranolol and samples were taken from the receiver chamber every 40 min for up to 4 h. For analysis, P app values were averaged over 4 h (six 40 min¯ux periods).…”
Section: Permeability Studiesmentioning
confidence: 99%
“…2). Colonic mucosae basal TEER values were 112 ± 32 Ω cm 2 (n = 29), again within the accepted range (29) In the presence of FITC-tripeptides, colonic TEER showed a small decrease of 9% over 120 min, but this was not different from controls. Addition of C 10 and uC 11 significantly decreased TEER, to just 3% and 8% of basal values respectively from between 5-120 min compared to tissues exposed to FITC-tripeptides alone (Fig.…”
Section: Mcfa Increase the Papp Of Fitc-tripeptides In Rat Jejunal supporting
confidence: 68%
“…It has been suggested that due to a reduced SA and higher abundance of tight junctions (i.e. assumed smaller paracellular area) in the colonic membrane, intestinal permeability and possibly absorption should be reduced compared to that in the SI (4,5,22,25,66,67). This was appropriately captured when the predictions were made using P eff,int , estimated by both M2 and M3, without affecting the overall f abs predictions (Figs.…”
Section: Discussionmentioning
confidence: 95%